Peranan Keluarga, Pemerintah, Masyarakat Dalam Pendidikan Anak - Mahardika, I Ketut; Salsabilah, Amelia; Distama, Rama Adhiyaksa Raka; Anggraeni, Wanda Dia Tri (Jurnal Ilmiah Wahana Pendidikan, 2024)
The environment is a place where a child grows and develops, so the environment plays a large role in shaping a person's personality and character. For most children, the family environment influences the child's development, followed by school and then society. Family is seen as an early environment built by parents and those closest to them. Every family is always different from other families, in this case what is different is, for example, the way the family is educated, the economic situation of the family. Every family has a history of struggles, values ​​and habits passed down from generation to generation which will subconsciously shape the child's character.